Examining the Validity of the Acs-Nsqip Risk Calculator in Plastic Surgery: Lack of Input Specificity, Outcome Variability and Imprecise Risk Calculations. (March 2017) - Johnson, Cassandra; Campwala, Insiyah; Gupta, Subhas
American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) created the Surgical Risk Calculator, to allow physicians to offer patients a risk-adjusted 30-day surgical outcome prediction. This tool has not yet been validated in plastic surgery. A retrospective analysis of all plastic surgery-specific complications from a quality assurance database from September 2013 through July 2015 was performed. Patient preoperative risk factors were entered into the ACS Surgical Risk Calculator, and predicted outcomes were compared with actual morbidities. The difference in average predicted complication rate versus the actual rate of complication within this population was examined. Within the study population of patients with complications (n=104), the calculator accurately predicted an above average risk for 20.90% of serious complications. For surgical site infections, the average predicted risk for the study population was 3.30%; this prediction was proven only 24.39% accurate. The actual incidence of any complication within the 4924 patients treated in our plastic surgery practice from September 2013 through June 2015 was 1.89%. The most common plastic surgery complications include seroma, hematoma, dehiscence and flap-related complications. The ACS Risk Calculator does not present rates for these risks. While most frequent outcomes fall into general risk calculator categories, the difference in predicted versus actual complication rates indicates that this tool does not accurately predict outcomes in plastic surgery. The ACS Surgical Risk Calculator is not a valid tool for the field of plastic surgery without further research to develop accurate risk stratification tools.